2000
DOI: 10.22358/jafs/68088/2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium picolinate, L-carnitine and thyroxine on the performance, nutrient digestibility and nitrogen balance in pigs weaned at 21 days of age

Abstract: A 3-week-growth trial was conducted to investigate the effects of chromium picolinate, L-carnitine, and thyroxine on the growth performance, nutrient digestibility, and N balance in starter pigs. Eighty starter pigs (Landrace x Yorkshire x Duroc, 21 ±2 days of age, 5.4 kg of average initial body weight) were employed in a completely randomized block design with four treatments: 1. Control: without additives, 2. CrP: control diet + 0.05% of chromium picolinate, 3. Carnitine: control diet + 0.5% of Camifeed(10%>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, Cho et al . [ 21 ] also observed improvement in availability of dry matter, crude protein and ash with 0.5% L-carnitine in diet of weaned pigs.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, Cho et al . [ 21 ] also observed improvement in availability of dry matter, crude protein and ash with 0.5% L-carnitine in diet of weaned pigs.…”
Section: Resultsmentioning
confidence: 95%
“…Real et al (2008), when studying pregnant and lactating sows provided with diets supplemented with L-carnitine (90 and 250 mg day -1 ) and chromium (360 to 1,000 µg day -1 ) using a factorial design, reported that such combinations at higher doses improved reproductive indices, particularly the number of live births in the first two parities, which suggests an additive effect of the supplements. The dietary association of chromium propionate (0.2 mg kg -1 of feed) with L-carnitine (500 mg kg -1 of feed) for piglets 21 days post-weaning led to improvements in performance characteristics (CHO et al, 2000). According to Woodworth et al (2007), the proposed mechanism of this joint action is based on the influence of chromium on glucose and insulin levels immediately after feeding and of carnitine on non-esterified fatty acids (an important metabolic fuel) 6 to 24 h after feeding, as well as the IGF concentration, which reduces body fat, changes lipid oxidation, and increases protein synthesis.…”
Section: Parametersmentioning
confidence: 99%